The Conflict Between Nestorians (Assyrians) and Chaldeans in the Foundation of Iraq - KAPLAN, YaÅŸar (Humanities Journal of University of Zakho, 2021)
Christians constitute an important component of Iraqi society. Iraqi Christians have been settled in Mesopotamia since ancient times. Christians have historical, political, cultural and social relations with both the Iraqi people and the people of Kurdistan. This community played an important role in the establishment and in the early period political administration of the Iraqi Republic. As it is known, the Christian community in Iraq and Kurdistan; It consists of two churches with different ideas, namely the Assyrian Church of the East and the Chaldean Catholic Church. During the Ottoman period, the Chaldean Church was residing in Mosul Province and the Assyrian Church of the East in Hakkari Sanjak of Van Province. While the Chaldean Church was under the influence of the French State, the Assyrian Church of the East was under the influence of the British State. From the middle of the 19th century, a noticeable competition started between both churches and communities, and powerful states were included in this competition in accordance with their policies. In this study, the relationship and competition between these two churches and communities at the dawn of the establishment of the Iraqi State will be discussed. In addition, the root of the ongoing problems among Christian components after the establishment of the Iraqi Republic will be pointed out. In this study, more Ottoman archive documents will be used.